Medical costs for patients with rheumatoid arthritis who have comorbid diabetes mellitus - Eiichi Tanaka; Eisuke Inoue; Ryoko Sakai; Katsuhiko Iwasaki; Ayako Shoji; Masayoshi Harigai (PLoS ONE, 2025)
Objectives To evaluate medical costs and resource use in patients with rheumatoid arthritis (RA) with and without diabetes mellitus (DM). Methods Data were obtained from the Japan Medical Data Center (JMDC) claims database. The baseline period comprised 6 months before the index date (first prescription date post-RA diagnosis) while the 12-month duration post-index date was the follow-up period. Patients with RA and DM prescribed an antidiabetic drug in the baseline period constituted the DM group, while patients with RA without DM or an antidiabetic prescription in the baseline and follow-up periods belonged to the non-DM group. Patients were matched by sex, age, Charlson Comorbidity Index (CCI), months from the first RA codes, and medications. The primary endpoint was total medical costs per patient in the follow-up period. The secondary endpoints were costs for drugs, treatments, and materials, their sub-categories, and proportions of patients using the sub-categories. Results One hundred and sixty-one DM group patients and 2,974 non-DM group patients were eligible for inclusion, and 109 patients were matched from each group. The median values of age and CCI were 59 years and 2.0 in both groups. After excluding DM-specific costs, both total medical costs and drug costs were significantly higher in the DM group compared with the non-DM group (total medical costs: DM/ non-DM: 5,163 USD/ 3,782 USD, P < 0.05; drug costs: DM/ non-DM: 2,242 USD/ 1,066 USD, P < 0.05) because of a higher proportion of biological disease-modifying antirheumatic drug (DMARD) users in the DM group (DM/ non-DM: 14.7%/ 5.5%). Treatment costs and material costs did not differ between the two groups. Conclusions Medical costs for RA were higher in the DM group than in the non-DM group because of a higher proportion of biological DMARD users.